Stochastic optimal preview control response of a quarter-car nonlinear suspension model using spectral decomposition method. (April 2022) - Gopala Rao, LVV; Sharma, Rakesh Chandmal; Satyanarayana, VSV; Palli, Srihari
This paper considers a two degree of freedom quarter-car model of a four wheel vehicle with nonlinear spring travelling at a constant speed on a random road surface with a preview control to obtain the optimal vehicle response. The nonlinear spring behavior is assumed as a hysteresis and modelled by the Bouc–Wen model. This nonlinear vehicle model is linearized by using statistical linearization approach. The root mean square values of the control force, suspension stroke and road holding characteristics are determined by spectral decomposition method. The results obtained for the equivalent linearized model using the SDM are validated with Monte Carlo simulation, and the results show that the vehicle performs better using preview control.